Knowledge, risk perceptions, and behaviors related to the COVID-19 pandemic in Malawi - Jethro Banda; Albert Dube; Sarah Brumfield; Abena Amoah; Amelia Crampin; Georges Reniers; Stephane Helleringer (Demographic Research, 2021)
Background: Behavioral changes are needed to limit the spread and mitigate the impact of the COVID-19 pandemic. Objective: We measured knowledge and behaviors related to COVID-19 during the early stages of the pandemic in Malawi (Southeast Africa). Methods: Using lists of phone numbers collected prior to the COVID-19 pandemic, we contacted a sample of adults by mobile phone in the six weeks after the first confirmed cases of COVID-19 were recorded in the country. We interviewed 619 respondents (79.5Š response rate). Results: Approximately half of respondents perceived no risk or only limited risk that they would become infected with the novel coronavirus. Contrary to projections from epidemiological models, a large percentage of respondents (72.2Š) expected to be severely ill if they became infected. Increased hand washing and avoiding crowds were the most frequently reported strategies used to prevent spreading SARS-CoV-2. The adoption of other protective behaviors (e.g., face masks) was limited. Respondents in urban areas had more accurate knowledge of disease patterns and had adopted more protective behaviors than rural respondents. Conclusions: In the first weeks of the pandemic, the adoption of preventive behaviors remained limited in Malawi, possibly due to low perceived risk of infection among a large fraction of the population. Additional information campaigns are needed to address misperceptions about the risk of infection with SARS-CoV-2 and the likelihood of severe illness due to COVID-19. Contribution: This study provides early data on behavioral responses to the COVID-19 pandemic in a low-income country.